Analisis Strategi Humas Dalam Meningkatkan Image Positif Pelayanan Administrasi di Kantor Kepala Desa Watudandang Kecamatan Prambon Kabupaten Nganjuk - Lutfiatul Kharima; Siti Sri Wulandari (Universitas Negeri Surabaya, 2020)
AbstractThis study aims to find out in depth about the work system of public relations and public relations strategies to improve the positive image of administrative services in the office of the head of Watudandang village, Prambon sub-district, Nganjuk district. This research is a qualitative research with descriptive research type and uses the case study methode. The sample in this study was the village head, secretary or public relations office of Watudandang village chief to determine the sample of researchers using purposive sampling techniques. Researchers collected data with in-depth interviews with public relations and the public who were using administrative services at the Watudandang village heads office. Watudandang village head as a triangulation of resources about the public relations work system and public relations strategy to enhance the positive image of administrative services. The analysis results obtained by researches that the work system implemented by the Watudandang village heads public relations office is structurally forming the village apparaturs and forming the cultural task of the village apparaturs called the pamong blok. Depth of the strategy that is used by the public relations of strategic is strategy that do public relations office of the village Watudandang the management of strategic. The strategy currently carried out by the Watudandang village heads public relations office is to approach the community by socualizing in very government program for the village. This causes the informations obtained by the community to be uneven, so researches provide advice to the Watudandang village heads public relations office to develop a service communications network to community by utilizing village website. Based on a system of work that is done by the public relations to draw up strategic improve the image positive service administration based on the phenomenon of research associate circuitry theory that the public relation will get the current image.Keywords: public relations strategy, positive image, administrative services